Designing of Inventory Control for Aluminum Industry - Ineu Widaningsih Sosodoro; Anastasia Lidya Maukar; Intan Puspita Pribadi (JIE Scientific Journal on Research and Application of Industrial System, 2018)
Inventory is one of important factors in manufacturing industry to ensure production process run. This research was conducted in an aluminum ingot manufacture company. The company faces a problem to manage the inventory system for their main raw material. The problem deals with the high expenditure due to safety stock that causes high inventory cost. Total inventory cost based on current condition is $270,706 per year. The proposed improvement method that used in this analysis is continuous review system. This method is applied to determine the appropriate Reorder Point (ROP) and to minimize the inventory cost. Based on the proposed improvement, total inventory cost can be reduced by 30%. This proposed system is also equipped with Decision Support System by using what-if analysis method as the tool to make decision for the next several periods by giving several scenarios and considering the aspects that influence to decision.Keywords: Inventory, Reorder point, Continuous Review System, Decision Support System, What If Analysis, Scenario